Legal Risk Management During Crisis at a Private Hospital in Malaysia - Rezza Khazrin Bin Kaman
This qualitative study involving Legal Risk Management (LRM) during the crisis at a Private Hospital in Malaysia hospital by concentrating on crisis management regarding the bomb threat & evacuation process. The LRM will be focusing on legal liability in crisis management. The objectives of the study are to identify the LRM in Organization, to determine Legal Risk Exposure during Crisis in Malaysian Hospital and to determine LRM during Crisis Management in Malaysian Hospital. Therefore, this LRM can be used as a guide for both Government Agencies and Private Sector for crisis management in the incident related to bomb threat and hospital evacuation. To date, there is no published literature that discussing the legal risk management in the context of crisis management involving bomb threat and patient evacuation. The study focusing 3 areas of law to identify legal risk which covers the law of tort, the law of evidence and insurance law. ISO 31000:2018-Risk management-Guidelines, IEC 31010:2019-Risk management-Risk assessment techniques and ISO 31022:2020-Risk management- Guidelines for the management of legal risk are the standard that has been used as the tools or guideline for research methodology. The findings of this study will be presented in the form of Legal Risk Identification Matrix (LRIM) and Legal Risk Register